2012
DOI: 10.1002/chem.201200412
|View full text |Cite
|
Sign up to set email alerts
|

Foamlike Porous Spinel MnxCo3−xO4 Material Derived from Mn3[Co(CN)6]2nH2O Nanocubes: A Highly Efficient Anode Material for Lithium Batteries

Abstract: A new facile strategy has been designed to fabricate spinel Mn(x)Co(3-x)O(4) porous nanocubes, which involves a morphology-conserved and pyrolysis-induced transformation of Prussian Blue Analogue Mn(3)[Co(CN)(6)](2)⋅nH(2)O perfect nanocubes. Owing to the release of CO(2) and N(x)O(y) in the process of interdiffusion, this strategy can overcome to a large extent the disadvantage of the traditional ceramic route for synthesis of spinels, and Mn(x)Co(3-x)O(4) with foamlike porous nanostructure is effectively obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…Some previous researches have demonstrated that increased pore size can improve electrochemical property, being displayed in mesoporous single-crystal Co 3 O 4 nano-needles and cobalt oxide nanowall arrays3334. Our research group has also reported that Co 3 O 4 porous nanocages and foamlike porous spinel nanopaticles with wide pore diameter distribution exhibited excellent Li-ion storage capability353637. Namely, it is necessary to modify the surface of electrode material and make sure that electrolyte can pass through the channel.…”
mentioning
confidence: 79%
“…Some previous researches have demonstrated that increased pore size can improve electrochemical property, being displayed in mesoporous single-crystal Co 3 O 4 nano-needles and cobalt oxide nanowall arrays3334. Our research group has also reported that Co 3 O 4 porous nanocages and foamlike porous spinel nanopaticles with wide pore diameter distribution exhibited excellent Li-ion storage capability353637. Namely, it is necessary to modify the surface of electrode material and make sure that electrolyte can pass through the channel.…”
mentioning
confidence: 79%
“…[61][62][63] It is worth mentioning that our fabrication process was distinct from the conventional synthesis methods, in which the metal oxides were usually obtained through calcination of PBAs precursors in air or O 2. 49,55 In our method, all processes were carried out at low temperature. Therefore, the shape and porous structure of the PBAs precursors were well retained and particles aggregation was significantly reduced.…”
Section: Synthesis Morphological Structural Characterizationmentioning
confidence: 99%
“…[1][2][3][4][5][6] The success of these applications strongly depends on the size of the hollow structure, and also on the nanostructure of the shell. [11][12][13][14][15][16][17] Therefore, the preparation of hierarchical hollow spheres with porous structure has been a research hot spot. [7][8][9][10] Moreover, porous materials are of great significance because porous materials with high porosity and specific surface area are able to interact with liquids not only at the surface, but also in the inner part of the bulk, and thus, porous materials generally exhibit enhanced chemical-physical performance over their solid counterparts.…”
Section: Introductionmentioning
confidence: 99%